Surface boundary-dendrite interactions in thin metallic Al-alloy samples. (1st March 2022) - Becker, Maike; Kolbe, Matthias; Steinbach, Sonja; Kargl, Florian
Abstract: Crystallographic orientations and growth directions of dendrites in thin Al-15 wt.%Cu (200 µm) and Al-29 wt.%Ge (500 µm) alloys were investigated employing in situ X-radiography and post-mortem X-ray tomography and electron backscatter diffraction. The Al-Cu alloy was solidified under microgravity conditions, while the Al-Ge sample was processed horizontally on ground. It was found that (i) dendrites nucleate on both sides of the surface in microgravity, but accumulate under normal gravity near the top surface due to buoyancy, (ii) dendrites grow along preferred in-plane crystallographic directions, which are 〈100〉 for Al-15 wt.%Cu and 〈100〉, 〈110〉 and 〈210〉 for Al-29 wt.%Ge, indicating that the solid-liquid interfacial anisotropy of this Al-Ge composition is similar for these 〈xy0〉 directions, (iii) slightly inclined dendrite arms in Al-Cu grow along the sample boundary after contact, whereas tips of inclined dendrite arms in Al-Ge never touch the boundary, but develop new primary tips originating from secondary branches. Graphical abstract: Image, graphical abstract